Digital Learning Environment Values of Pre-Service Teachers as a Basis for Successful Professional Self-Realisation: A Case Study - Olga Yakovleva (MDPI AG, 2022)
The paper analyses the value mindsets of pre-service teachers in terms of the digital learning environment (DLE). DLE is considered to be both a system of new tools and methods for teaching activity and a prospective educational eco-system for learning. The DLE value model is based on a psychodidactic approach, which concerns three main constructs-digital content values, communication values, and management values. The research involved 200 pre-service teachers who were asked to complete a questionnaire, evaluating 27 DLE values and opportunities. The results show that pre-service teachers value digital learning content but are not sufficiently ready for its creation; they develop tolerance in communication yet do not have enough skills to show empathy; they appreciate independence in learning management and still need training in professional digital self-presentation. Consequently, professional training and especially internships for pre-service teachers should include a synthesis of traditional (face-to-face) and virtual communication and interaction with children to facilitate mastering an expanded set of competencies for successful professional self-realisation. The findings can be beneficial in terms of e-learning practices, DLE design, and the organisation of internships.